2016
DOI: 10.1080/15548627.2016.1179402
|View full text |Cite
|
Sign up to set email alerts
|

SLC35D3 increases autophagic activity in midbrain dopaminergic neurons by enhancing BECN1-ATG14-PIK3C3 complex formation

Abstract: Searching for new regulators of autophagy involved in selective dopaminergic (DA) neuron loss is a hallmark in the pathogenesis of Parkinson disease (PD). We here report that an endoplasmic reticulum (ER)-associated transmembrane protein SLC35D3 is selectively expressed in subsets of midbrain DA neurons in about 10% TH (tyrosine hydroxylase)-positive neurons in the substantia nigra pars compacta (SNc) and in about 22% TH-positive neurons in the ventral tegmental area (VTA). Loss of SLC35D3 in ros (roswell muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…A recent study showed that SLC35D3 (solute carrier family 35, member D3), as a regulator of tissuespecific autophagy, increases autophagic activity in midbrain dopaminergic neurons via enhancing BECN1-ATG14-PIK3C3 complex formation. 42 It would be rewarding to test whether this process was also involved in the morphine-induced dopaminergic neuron-specific autophagy in the midbrain.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that SLC35D3 (solute carrier family 35, member D3), as a regulator of tissuespecific autophagy, increases autophagic activity in midbrain dopaminergic neurons via enhancing BECN1-ATG14-PIK3C3 complex formation. 42 It would be rewarding to test whether this process was also involved in the morphine-induced dopaminergic neuron-specific autophagy in the midbrain.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that disrupted autophagy flux contributes to neuronal cell injury and death in brain of patients with neurodegenerative diseases, including amyotrophic lateral sclerosis, PD‐like dementia, and Huntington's disease . Thus, we next investigated whether autophagy implicated in ox‐LDL‐induced HT‐22 cell injury and apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…Recent research indicates that SLC35D3 is involved in the biogenesis of platelet dense granules, and the expression of SLC35D3 in the brain was limited to expressing D1R rather than D2R [20][21][22]. Other results suggest that SLC35D3 is a new regulator of tissue-specific autophagy and plays an important role in the increased autophagic activity required for the survival of subsets of DA neurons [23]. Moreover, reports on the expression and structure of the SLC35D3 gene are not available in swine [24].…”
Section: Introductionmentioning
confidence: 86%